KAJIAN KESELAMATAN PENGGUNA KENDARAAN BERMOTOR KHUSUS SKUTER LISTRIK DI KAWASAN ALUN-ALUN KOTA TEGAL (FSTPT Indonesia, 2023)
Electric scooters have become popular in Indonesia since 2019. Direct research conducted by Grab Indonesia on 3,107 users, the results showed that 81% of respondents agreed that GrabWheels added to the attraction of visitors, but as reported by tempo.com 80.2% of the 249 respondents had accidental falls. The purpose of this study is to find out to what extent the safety aspects of electric scooters are met as stated in the Regulation of the Minister of Transportation Number 45 of 2020 concerning Special Motorized Vehicles as information that can be used by the government in evaluating existing regulations and preparing alternative transportation management that is more suitable, using the observation method, interviews, and questionnaires. The results show that more than 50% of the electric scooters rented in the Tegal Square area are safe, from the aspect of electric scooter tenants, almost all of them have provided helmets but all rental places take the road. Judging from the behavioral aspect of electric scooter users, half of them still carry passengers and do not use helmets, but almost all of them have paid attention to the safety of other road users and focus on driving. ABSTRAK Skuter listrik mulai popular di Indonesia sejak 2019. Riset langsung yang dilakukan Grab Indonesia kepada 3.107 pengguna, hasilnya 81% responden setuju bahwa GrabWheels menambah daya tarik pengunjung, namun dilansir dari tempo.com 80,2% dari 249 responden mengalami kecelakaan terjatuh. Tujuan penelitian ini mengetahui sejauh mana aspek keselamatan skuter listrik dipenuhi sebagaimana tercantum dalam Peraturan Menteri Perhubungan Nomor 45 Tahun 2020 Tentang Kendaraan Bermotor Khusus sebagai informasi yang bisa digunakan pemerintah dalam evaluasi peraturan yang sudah ada dan penyusunan alternatif manajemen transportasi yang lebih sesuai, menggunakan metode observasi, wawancara, dan kuesioner. Hasil menunjukkan bahwa lebih dari 50% skuter listrik yang disewakan di kawasan Alun - Alun Tegal sudah berkeselamatan, dilihat dari aspek penyewa skuter listrik hampir seluruhnya sudah menyediakan helm namun semua tempat sewa mengambil badan jalan. Dilihat dari aspek perilaku pengguna skuter listrik, separuhnya masih mengangkut penumpang dan tidak menggunakan helm, namun hampir seluruhnya sudah memperhatikan keselamatan pengguna jalan lain dan fokus berkendara.